2010
DOI: 10.1152/ajpregu.00591.2009
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin activity in the amygdala controls appetite for dietary fat

Abstract: The amygdala is rich in melanocortin 4 receptors. Because the reduction in dietary fat intake after enterostatin is injected in the central nucleus of the amygdala (CeA) is blocked by a melanocortin 4 receptor antagonist, we investigated the role of melanocortin activity in the CeA in regulating food intake and macronutrient choice. Sprague-Dawley rats, fitted with CeA cannulas, were fed either chow, a high-fat (HF) diet, or adapted to a two-choice HF or low-fat (LF) diet. Injections of the MC4R agonist melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 62 publications
6
54
0
5
Order By: Relevance
“…5A: control vs. AGRP: F 1,12 ϭ 7.00, P ϭ 0.03; control vs. SHU-9119: F 1,12 ϭ 6.66, P ϭ 0.03). As expected (11), Bdnf mRNA levels were increased in the hypothalamus after intracerebroventricular injection of either AGRP or SHU-9119 (Fig. 5B: control vs. AGRP: F 1,12 ϭ 6.39, P ϭ 0.03; control vs. SHU-9119: F 1,12 ϭ 10.94, P ϭ 0.01).…”
Section: Inhibition Of Melanocortin Signaling Increased Food Intake supporting
confidence: 81%
See 1 more Smart Citation
“…5A: control vs. AGRP: F 1,12 ϭ 7.00, P ϭ 0.03; control vs. SHU-9119: F 1,12 ϭ 6.66, P ϭ 0.03). As expected (11), Bdnf mRNA levels were increased in the hypothalamus after intracerebroventricular injection of either AGRP or SHU-9119 (Fig. 5B: control vs. AGRP: F 1,12 ϭ 6.39, P ϭ 0.03; control vs. SHU-9119: F 1,12 ϭ 10.94, P ϭ 0.01).…”
Section: Inhibition Of Melanocortin Signaling Increased Food Intake supporting
confidence: 81%
“…To determine whether and where NENF may function with the BDNF and melanocortin signaling pathways, we used an experimental paradigm based on studies of Boghossian et al (11), who demonstrated that AGRP delivery to the amygdala increases Bdnf mRNA levels after allowing animals 2 h of food access following injection. We hypothesized that central delivery of AGRP or SHU-9119 would induce increased food intake, and this, in turn, would induce hypothalamic Nenf gene expression as a signal to reduce food intake, likely in response to satiety factors.…”
Section: Inhibition Of Melanocortin Signaling Increased Food Intake mentioning
confidence: 99%
“…Furthermore, infusion of MC4R agonists decreases food intake, whereas antagonism results in increased food intake (Rossi et al, 1998). Interestingly, alpha melanocyte-stimulating hormone (α-MSH) and the MC4R are abundantly expressed not only in hypothalamic nuclei but also in the amygdala and, when administered into the CeA, MC4R agonists inhibit feeding (Boghossian et al, 2010;Kask and Schioth, 2000b), suggesting a role for CeA MC4R in the regulation of feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Blockade or absence of MC4R induces hyperphagia, reduced energy expenditure and obesity (Balthasar et al, 2005;Butler and Cone, 2003). Interestingly, MC4R are expressed not only in the hypothalamus but also in the amygdala (Mountjoy et al, 1994); melanocortin signaling in the CeA can indeed regulate feeding behavior bidirectionally, with MC4R exerting a tonic inhibitory role on feeding (ie, producing anorexia) (Boghossian et al, 2010;Kask et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…Similar experiments in the mouse demonstrate that the MC3R/MC4R agonist MTII acutely decreased intake of fat, but not carbohydrate or protein, in a three-choice diet model (9). The consumption of dietary fat in a two-choice model may also be increased by administration of MC3R/MC4R antagonists AgRP or SHU9119 directly into the central nucleus of the amygdala (CeA) (10). The amygdala has been demonstrated to play a role in emotion, reward, and motivation (11), and several studies link the amygdala to macronutrient preference and intake (10,12,13).…”
mentioning
confidence: 86%